COVID associated mucormycosis and its etiopathological correlation - Sachdeva, Kavita; Shukla, Amrita; Kabade, Mayur V.; Chandrakapure, Deepankar; Tom, Stephy Maria; Raj, Lakshmy V. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: During COVID-19 pandemic, patients with diabetes mellitus (DM) and immunocompromised condition were at risk of opportunistic infections among which mucormycosis came with most dreadful consequences. Mucormycosis is a potential life-threatening, opportunistic fungal infection caused by fungi belonging to the order mucorales. Most vulnerable patients at risks are observed to be patients with uncontrolled blood sugar and diabetic ketoacidosis (DKA), patients with immunocompromised state, severe neutropenia in viral infections, on steroid therapy, oxygen therapy, chemotherapy. Despite aggressive and disfiguring surgeries paired with antifungal therapy, the mortality and morbidity rate are high. The mentioned epidemiological factors were observed and correlation between these were analysed to avoid the predisposing factors in future. Methods: The study was conducted over 160 patients as prospective cross-sectional design, admitted in mucor ward of NSCB and MCH, Jabalpur. Patients were assessed clinically with related investigations. Consent was taken after explaining the nature and purpose of study. Results: In our study, mucormycosis was found to affects elderly males more commonly, with immune-compromised state especially in diabetic population, received unsupervised steroid or oxygen therapy in unhygienic setups. Conclusions: To ensure better outcome, along with early surgical intervention and medical management, environmental predisposing factors must be taken care of. Immunocompromised state especially uncontrolled diabetes and acidosis should be corrected, judicial use of steroids, healthy life style, oxygen supplementation with aseptic masks and tubings, use of distilled water in humidifiers, immunity build-up may bring a major change in prognosis.